Research on factors influencing the performance of public health governance in the ethnic areas of Sichuan Province: a study based on the TOE framework - Shi, Yuke; Chen, Dandi; Zhou, Jing (Frontiers in Public Health, 2025)
IntroductionTo better improve the performance of public health governance of the government of ethnic areas in Sichuan Province, and to promote the high-quality development of health and health care in the area.MethodsQualitative comparative analysis of fuzzy sets and analysis of necessary conditions.ResultsBig data technology, ecological environment and public opinion environment have a significant impact on the public health governance performance of ethnic area governments in Sichuan Province when they play a major role respectively; the synergistic combination of the three conditions of technology, organization and environment is conducive to the improvement of the public health governance performance of ethnic area governments in Sichuan Province.SuggestionsDevelop digital economy; improve ecological environment; strengthen public opinion management; exert synergistic governance effect of technological, organizational and environmental conditions.